Myanmar endemic Burmorthacris subaptera Kevan, Singh et Akbar, 1964 (Pyrgomorphidae: Orthacridini) rediscovered after 85 years - Sirichantakul, Kavee; Hmone, Zune Wit; Kyaw, Mar Lar; Thandar, Cho (Zootaxa, 2024)
A curious micropteous gaudy grasshopper (family Pyrgomorphidae), Burmorthacris subaptera was described by Kevan, Singh and Akbar in 1964 as a sole member of its genus based on a female and a male collected in Yenangyaung (upper Myanmar) on 27th and 28th August 1937 and which were deposited at the Academy of Natural Sciences of Philadelphia. The species has never been reported since then. The genus Burmorthacris is the northernmost of the Orthacris genus group genera, which includes mostly genera from Sri Lanka and Malaysia. Recently we rediscovered this B. subaptera in its type locality (Yenangyaung township in the Magway Region) in Myanmar, 85 years after the holotype and the paratype were collected in the same place, and furthermore herewith we present one more locality in another region where the species has been found (Nyaung-U township in the Mandalay Region). Due to the lack of basically any information on this species distribution and habitat, including also photographs of its natural coloration in this habitat, the present study provides the first-time photographs of B. subaptera in its natural habitat from both localities, as well as some insights into its morphology, especially coloration, habitat, and behavior.